2021
DOI: 10.3390/molecules26175343
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of 2D Layered Graphene Oxide and 3D Porous Cellulose Heterogeneous Membranes for Nanofluidic Osmotic Power Generation

Abstract: Salinity gradient energy, as a type of blue energy, is a promising sustainable energy source. Its energy conversion efficiency is significantly determined by the selective membranes. Recently, nanofluidic membrane made by two-dimensional (2D) nanomaterials (e.g., graphene) with densely packed nanochannels has been considered as a high-efficient membrane in the osmotic power generation research field. Herein, the graphene oxide-cellulose acetate (GO–CA) heterogeneous membrane was assembled by combining a porous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 56 publications
0
14
0
1
Order By: Relevance
“…This interesting phenomenon arising from overlapping EDL in the ion transport regions results in ion enrichment in the confined spaces, where the ion transport behavior is determined by the surface and space charges of the TFC membranes rather than by the bulk concentration. 4,40 It is found that the current densities of the TFC membranes gradually decrease when increasing load resistance (Figure 4D), and the output power density reached its peak value when the load resistance was approximately 20 kΩ (Figure 4E). Compared with PVA or SPEEK-PVA membranes, the SPEEK/G-PVA TFC membrane showed the highest output power density of 5.89 W m −2 (Figure 4E,F).…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This interesting phenomenon arising from overlapping EDL in the ion transport regions results in ion enrichment in the confined spaces, where the ion transport behavior is determined by the surface and space charges of the TFC membranes rather than by the bulk concentration. 4,40 It is found that the current densities of the TFC membranes gradually decrease when increasing load resistance (Figure 4D), and the output power density reached its peak value when the load resistance was approximately 20 kΩ (Figure 4E). Compared with PVA or SPEEK-PVA membranes, the SPEEK/G-PVA TFC membrane showed the highest output power density of 5.89 W m −2 (Figure 4E,F).…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Above this point, the ionic conductance follows the bulk rule of linearly increasing with concentration due to the thin electrical double layer (EDL). , While when the concentration is below the critical point, a strong nonlinear relationship is observed, and the ionic conductivity deviates sharply from the bulk value, reaching a plateau. This interesting phenomenon arising from overlapping EDL in the ion transport regions results in ion enrichment in the confined spaces, where the ion transport behavior is determined by the surface and space charges of the TFC membranes rather than by the bulk concentration. , It is found that the current densities of the TFC membranes gradually decrease when increasing load resistance (Figure D), and the output power density reached its peak value when the load resistance was approximately 20 kΩ (Figure E). Compared with PVA or SPEEK-PVA membranes, the SPEEK/G-PVA TFC membrane showed the highest output power density of 5.89 W m –2 (Figure E,F).…”
Section: Resultsmentioning
confidence: 95%
“…A graphene oxide nanosheet is decorated with epoxy, phenyl hydroxyl and carboxylic groups, which renders a negative surface charge in a hydrated state. The vacuum filtration of a dispersion with exfoliated graphene oxide nanosheets is a common way to prepare the graphene oxide stack [ 85 ]. Owing to the high aspect ratio, the graphene oxide nanosheets stack horizontally, which forms a paper-like layered structure.…”
Section: Emerging Porous Membranesmentioning
confidence: 99%
“…10 GOMs, being one of the most typical 2D nanofluidic membranes, possess densely packed 2D nanochannels functionalized with oxygen-containing groups, making them highly promising for applications in energy conversion and storage. [30][31][32][33][34] Additionally, the bandgap of GO can be adjusted by changing the content of oxygen-containing groups, rendering it suitable for photoelectric applications. [35][36][37] To further enhance the performance of GOMs, we explored slightly reduced vertical GOMs, featuring short channel lengths and efficient light absorption for better photo-driven ion pump properties.…”
Section: Introductionmentioning
confidence: 99%